KEPUASAN GURU SMA DESA BOBOJONG TERHADAP PELATIHAN PENGEMBANGAN INSTRUMEN PENILAIAN AUTENTIK UNTUK MENINGKATKAN PROFESIONALISME GURU - Arthur, Riyan; Tjalla, Awaluddin; Supriyatti, Yetti; Sarifah, Iva (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This service is carried out on the basis of the lack of understanding of educators in making assessment instruments. As well as the many inability of educators in compiling appropriate assessment assessments for their students. This service is a mentoring activity to increase the professionalism of high school teachers in developing authentic assessment instruments that aim to improve the ability of teachers to make assessment instruments. This service partner is a high school (SMA) located in Bobojong Village, Mande District, Cianjur Regency, West Java. With a focus on activities, namely assisting the development of assessment instruments for high school teachers. The methods used in this activity include lectures, discussions, direct demonstrations, questions and answers, and assignments. These methods are carried out by adjusting the situation and conditions in the classroom. The target to be achieved in the implementation of this activity is to improve the ability of high school teachers in Bobojong Village, Mande District, Cianjur Regency, West Java. in compiling the assessment instrument. In addition, as an outcome, coaching participants are expected to be able to use good assessments when administering education to evaluate the quality of program achievements. We use 2 stages of Kirkpatrick's evaluation, namely reaction and learning. The reaction evaluation is to determine the participants' reactions to the implementation of the training, while the learning evaluation is to measure the abilities obtained before and after the training.